How to manage a brand to be strong: a study of Zara - luo, danye (2008)
The meaning that a brand stands for is extremely significant for consumers, so a considerable number of researchers (Philips, 1988; Murphy, 1990; Brymer and Schiro, 1989; Temporal, 2002) are increasingly interested in brand management. The main purpose of this study is to investigate how a brand is managed to become a strong brand. The study will commence with an analysis of several key elements in the management of a brand. The three major instruments of a brand strategy are: positioning and brand values choice; brand images; and added value. If corporations exploit some brands into more than one market, the development of a brand portfolio, extension and endorsement strategy may be used (Riezebos et al., 2003; Riezebos, 1995b; Temporal, 2002). Zara is a good case study to show how the brand has been managed to become a powerful brand in the fashion industry (Tungate, 2005). A combination of qualitative (case study) and quantitative questionnaire survey) methods will be employed to ascertain whether Zara's success is in terms of vital elements, as mentioned above, in the brand management. Research suggests that a brand with accurate positioning and brand values choice, positive brand image and high brand-added value, should become a powerful brand. Brand name, design and advertising have an important influence on this progression. A brand portfolio, brand extension and endorsement strategy can be used to develop brands for entry into other markets. If these strategies are managed well, a brand can also become stronger. Key words: brand management, positioning, brand values, brand images, brand-added value, a brand portfolio, extension and endorsement strategy, Zara.